2022
DOI: 10.3389/fimmu.2022.829433
|View full text |Cite
|
Sign up to set email alerts
|

Flaviviruses: Innate Immunity, Inflammasome Activation, Inflammatory Cell Death, and Cytokines

Abstract: The innate immune system is the host’s first line of defense against the invasion of pathogens including flavivirus. The programmed cell death controlled by genes plays an irreplaceable role in resisting pathogen invasion and preventing pathogen infection. However, the inflammatory cell death, which can trigger the overflow of a large number of pro-inflammatory cytokines and cell contents, will initiate a severe inflammatory response. In this review, we summarized the current understanding of the innate immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 191 publications
(236 reference statements)
0
17
0
Order By: Relevance
“…Through recognition of these PAMPs by pattern-recognition receptors (PRRs), flaviviruses in general, and WNV in particular can induce an antiviral response leading to the secretion of interferons (IFNs) and inflammatory cytokines (e.g. type-I IFN, TNF-α, IL-1β, IL-6, IL-10) [ 28 ]. These mechanisms, besides the control of viral propagation, can participate in systemic inflammation and exacerbate clinical onset.…”
Section: Introductionmentioning
confidence: 99%
“…Through recognition of these PAMPs by pattern-recognition receptors (PRRs), flaviviruses in general, and WNV in particular can induce an antiviral response leading to the secretion of interferons (IFNs) and inflammatory cytokines (e.g. type-I IFN, TNF-α, IL-1β, IL-6, IL-10) [ 28 ]. These mechanisms, besides the control of viral propagation, can participate in systemic inflammation and exacerbate clinical onset.…”
Section: Introductionmentioning
confidence: 99%
“…In the mammalian host, the type I response was shown to be important in the antiviral response against CHIKV and dengue virus infection ( 122 , 123 ). However, studies with mice have shown that this response is sensitive to temperature fluctuations during CHIKV infection, demonstrating in particular a reduced response against viral infection at suboptimal temperatures ( Fig.…”
Section: Effect Of Temperature On Innate Immune Responsementioning
confidence: 99%
“…Innate immunity is able to clear the virus in the upper airways of COVID-19 patients in the first 10-12 days from infection, inducing the resolution of the infection [34] in the majority of individuals [35]. Innate immune cells (macrophages, monocytes, dendritic cells, neutrophils, NK cells, and γδ T cells) expressed several PRRs that recognize PAMPs or damage-associated molecular patterns (DAMPs) and trigger inflammatory signaling pathways and immune responses to fight the virus [36]. In COVID-19 patients, we observed an increased production of inflammatory cytokines paralleled with an increase in myeloidderived suppressor cells (MDSC).…”
Section: Severe Acutementioning
confidence: 99%